BUKTI-BUKTI PROSES ISLAMISASI DI KESULTANAN PALEMBANG - Endang Rochmiatun (Fakultas Adab dan Humaniora UIN Raden Fatah, 2017)
When is Islam into Palembang is not surely, without else still conflict, because any more arguments. Distribution of Islam in Palembang can do it the way of the peace, and then continues step by step. Islamisasi process can do it tool, like as economic of way, married of the way and tassawuf. more than factually Islam into Palembang, so that signed like as mosque, grave, town center and then manuscript. Key word: Kapan Islam Masuk di Palembang, Proses Islamisasi, Bukti Islam di Palembang